Obesity and the onset of depressive symptoms among middle-aged and older adults in China: evidence from the CHARLS - Huiqiang Luo; Jijie Li; Qi Zhang; Peiya Cao; Xiaohui Ren; Aiping Fang; Haiying Liao; Lijuan Liu (BMC, 2018)
Abstract Background The association between obesity and depression has been documented in previous systematic studies but remains controversial. Many prospective studies have focused on children and youth, and several studies have examined this relationship among older populations. This study of the changes in obesity status aimed to examine the association between depression and obesity among middle-aged and elderly adults in China. Methods The data originated from the follow-up survey (2011 and 2013-2015) of the China Health and Retirement Longitudinal Study (CHARLS) and included 3337 residents aged at least 45 years who completed a physical examination and were evaluated with the Center for Epidemiological Studies Depression Scale (CES-D-10), which assessed depressive symptoms. Obesity status was defined by body mass index (BMI) and waist circumference (WC) according to Chinese criteria. A time-dependent Cox proportional hazards model was used to estimate the relationship between obesity status and depressive symptoms. Results The rate of depression in men and women was 26.67 and 38.37%, respectively. Based on BMI, the proportion of the population that was overweight and obese was 28.07 and 9.26%, respectively, in males and 35.03 and 16.84%, respectively, in females. Males with obesity were less likely to suffer from depressive symptoms than males with a normal weight (ORHR = 0.506, 95% CI = 0.347~ 0.736). Based on WC, the proportion of abdominal obesity was 49.35% in males and 73.65% in females. Males with abdominal obesity were less likely to suffer from depressive symptoms than males without abdominal obesity (ORHR = 0.775, 95% CI = 0.644~ 0.933). Conclusion Obesity is more likely to be associated with the onset of depression in males than in females. However, regardless of underweight or overweight status, the relationship between weight and depressive symptoms is negatively associated among females and males. In conclusion, both BMI and WC can be used as tools for examining the association between obesity and depression.